THE IMPLEMENTATION OF NETWORK SERVER SECURITY SYSTEM USING HONEYPOT - Faldi Faldi; Dinamita Romadoni; Muhammad T Sumadi (JIKO (Jurnal Informatika dan Komputer), 2023)
Network Server security is an important aspect of ensuring the integrity and availability of information systems. This research aims to implement network Server security at Muhammadiyah University of East Kalimantan using Honeypot technology. Honeypots are used to attract the attention of attacks and monitor suspicious activities on the network. The research method used is NDLC (Network Development Life Cycle), which includes the design and implementation of Honeypots, as well as the collection and analysis of detected attack data. The research results show that by using three attack techniques, namely Slowloris attack with a Honeypot processing time of 2 seconds and Snort processing time of 180 seconds, GoldenEye attack with a Honeypot processing time of 2 seconds and Snort processing time of 180 seconds, and LOIC tools with a Snort processing time of 180 seconds. Honeypots cannot identify DDoS attacks because they focus more on attacks such as penetration attempts or other suspicious activities.